ANALISIS POLA NATURE OF MODELS (NOM) DALAM BUKU SISWA BIOLOGI KELAS X - Nur Amalina Susanti; Fenny Roshayanti; Lussana Rossita Dewi (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2021)
This research is entitled "Analysis of Nature of Models (NoM) Patterns in the Biology Student Book Class X". This study aims to determine the pattern of using the type of model and the characteristics of Nature of Models (NoM) contained in the Biology class X student book. The sample in this study was the dominant book used in SMA N throughout Magelang Regency in the class X student book. to model types and characteristics of Nature of Models. The data obtained were then analyzed using descriptive analysis. The results showed that the type of model which consisted of 8 types, the type of scale was found more, namely as much as 113 or 64% compared to other types of models. Inversely proportional to the type of mathematical model that is not found in student books. While the characteristics of Nature of Models in the illustration category, the structural model sub-category dominates as much as 72.31%, the complexity aspect of the fact sub-category dominates as much as 77.40%, the low abstraction category dominates as much as 74.01%, and all models found are in accordance with learning objectives. The results of the analysis of the Nature of Models pattern in the Biology class X student book are in accordance with the characteristics of Biology.   Abstrak. Penelitian ini berjudul "Analisis Pola Nature of Models (NoM) dalam Buku Siswa Biologi Kelas X". Penelitian ini bertujuan untuk mengetahui pola penggunaan tipe model dan karakteristik Nature of Models (NoM) yang terdapat dalam buku siswa Biologi kelas X. Sampel dalam penelitian ini adalah buku yang dominan digunakan di SMA N se-Kabubaten Magelang pada buku siswa kelas X. Analisis difokuskan terhadap tipe model dan karakteristik Nature of Models. Data yang diperoleh selanjutnya dianalisis menggunakan analisis kualitatif. Hasil penelitian menunjukan bahwa tipe model yang terdiri dari 8 tipe, tipe skala lebih banyak ditemukan, yaitu sebanyak 113 atau 64% dibandingkan tipe model lainnya. Berbanding terbalik dengan tipe model matematik yang tidak ditemukan dalam buku siswa. Sedangakan karakteristik Nature of Models pada kategori ilustrasi, subkategori model struktural lebih mendominasi sebanyak 72,31%, aspek kompleksitas subkategori fakta mendominasi sebanyak 77,40%, aspek abstraksi rendah lebih mendominasi sebanyak 74,01%, dan seluruh model yang ditemukan telah sesuai dengan tujuan pembelajaran. Hasil analisis pola Nature of Models dalam buku siswa Biologi kelas X tersebut sesuai dengan ciri-ciri Ilmu Biologi.